الأبعاد الاستراتيجية للصواريخ الباليستية الإيرانية - بن زيدان, شريفة; طيبي, محمد بلهاشمي الأمين (جامعة الوادي University of Eloued, 2019)
تشكل الصواريخ الباليستية إحدى مكونات البرنامج النووي الإيراني،حيث تتبعها إيران لفرض مكانتها في الشرق الاوسط،خاصة وأنها تنتمي إلى النظام الإقليمي الخليجي كنظام فرعي يتواجد ضمن هذه المنطقة التي تعتبر من أهم المناطق الجيوسياسية الحساسة. فالأبعاد الإستراتيجية للترسانة الصاروخية الإيرانية تتوزع بين الأبعاد الأمنية والسياسية وحتى الإيديولوجية.تهدف إلى الحفاظ على الحد الأقصى من البقاء ومكسب لإبراز هيبتها، ولعبها دور القوة التعديلية في منطقة الشرق الأوسط من خلال تغيير الوضع الراهن وفق منظورها الواقعي وتبني سياسات إقليمية واستخدام صواريخها كأداة للردع والضغط على القوى الكبرى بل و مساومتها في قضايا إقليمية كما تهدف إلى تبني سياسات دفاعية-هجومية ومواكبة الدول التي تشهد سباقا نوويا. The ballistic missiles are one of the components of Iran's nuclear program developped by Iran to impose its position in the Middle East. especially as it exist in the Gulf regional system as a subsystem located within this region,which is one of the most important geopolitical areas. The strategic dimensions of Iran's missile arsenal are divided between security, political and even ideological dimensions, aim to maintain maximum survival and also gain prestige. and play the role of revisionist power in the Middle East by changing the current situation according to its realistic perspective and adopting regional policies and using its missiles as a deterrent,pressure on Major powers and bargaining them in many regional issues, as well as to adopt defensive and offensive policies and Convoying with the countries that are knowing a nuclear race.
Keywords: إيران ; الصواريخ الباليستية ; الأبعاد الإستراتيجية ; الردع ; الأمن الإقليمي; Iran ; ballistic missiles ; strategic dimensions ; deterrence ; regional security